A Case of Delusional Infestation in Primary Health Care - João, Sara (2024)
Delusional infestation is a disorder characterized by the persistent belief of infestation by living or inanimate organisms, although there is no evidence for that. In the presence of complaints, patients often seek medical advice from a family doctor or a dermatologist, rather than a psychiatrist, since they do not believe that their symptoms are delusional. We describe the case of an 86-year-old female patient who presented to primary health care with a history of delusional ideas of infestation with visual and cenesthetic hallucinations. After an etiological investigation, the case was discussed with a psychiatrist from the local hospital. The patient was diagnosed with delusional infestation and started risperidone, with complete remission of symptoms. This case intends to emphasize the need for family doctors to recognize this pathology in order to be able to manage it correctly. It also reinforces the importance of communication between different specialties in the management of disorders like this, which correspond to rarer disorders,